Penerapan Pelayanan Prima di Dinas Perpustakaan dan Arsip Kabupaten Ciamis - Wina Hidayati; Verra Rosyalia Widia Sofyan (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
Excellent service is an important aspect in improving the quality of services in public institutions, including regional libraries. The implementation of optimal service plays a role in creating satisfaction and increasing public trust in the institution. This study aims to describe and analyze the implementation of excellent service at the Department of Library and Archives of Ciamis Regency. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation and interviews with library visitors. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the service has been implemented quite well based on the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Adequate physical facilities and the friendly and responsive attitude of staff are the main supporting factors. However, several obstacles remain, such as limited internet access, a limited number of computers, and staff availability at certain times. Therefore, improvements in infrastructure and human resource competencies are needed to support sustainable improvement in library service quality. The results of this study are expected to serve as a reference for improving the quality of library services.